Service Satisfaction Based on Performance Index and Importance Performance Analysis (IPA) - Hermanto Hermanto; Riza Bahtiar Sulistyan; Hassan Touati (Mahameru Publisher, 2022)
Evaluation of service performance is something that needs to be done regularly in order to improve its quality. This research is intended to measure the level of satisfaction or expectations of lecturers and users by using ten service elements as measurement items, with a sample of 80 respondents in XyZ University. To meet the feasibility of the instrument, validity and reliability tests were carried out. The analysis technique was quantitative descriptive through the Index and Importance Performance analysis. The results showed that the level of lecturer satisfaction was in the category of good satisfaction with high expectations, several service elements that needed attention and improvement were; elements of funding sources, providing research facilities and community service proportionally according to needs and achieving service promises in accordance with the research and community service strategic plans that have been proclaimed.